1983
DOI: 10.1128/aac.23.6.935
|View full text |Cite
|
Sign up to set email alerts
|

In vitro susceptibility of Mycobacterium fortuitum to amoxicillin or cephalothin in combination with clavulanic acid

Abstract: The comparative in vitro activity of cefoxitin, cephalothin, amoxicillin, and clavulanic acid in combination with the latter two agents against 13 isolates of Mycobacterium fortuitum was evaluated by agar dilution susceptibility testing.Amoxicillin was more active than cephalothin but less active than cefoxitin against the strains tested. Clavulanic acid in combination with these 3-lactams usually improved the activity by one or two dilutions compared with the P-lactams alone.Cefoxitin and cefmetazole, two cep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Some early published mhethods did use more standard bacterial techniques but used media that were considered best for the growth of mycobacteria (1,10,12,15,16). Since 1978, however, more investigators have begun testing these species with standard methods recommended for testing other rapidly growing bacteria, e.g., Enterobacteriaceae and staphylococci (2)(3)(4)(5)(6)(7)(20)(21)(22)(23)(24). We have previously shown that agar and broth microdilution methods work well when applied to M. fortuitum and M. chelonae (19) and that antimicrobial agents other than antituberculosis agents should be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Some early published mhethods did use more standard bacterial techniques but used media that were considered best for the growth of mycobacteria (1,10,12,15,16). Since 1978, however, more investigators have begun testing these species with standard methods recommended for testing other rapidly growing bacteria, e.g., Enterobacteriaceae and staphylococci (2)(3)(4)(5)(6)(7)(20)(21)(22)(23)(24). We have previously shown that agar and broth microdilution methods work well when applied to M. fortuitum and M. chelonae (19) and that antimicrobial agents other than antituberculosis agents should be tested.…”
Section: Discussionmentioning
confidence: 99%
“…␤-Lactamases have been described for most isolates of pathogenic mycobacteria with the exception of members of the M. avium complex (1, 16, 19, 33). Use of the combination of ␤-lactam antibiotics with various ␤-lactamase inhibitors has been shown to be synergistic against a number of mycobacterial species (3,6,7,27).…”
Section: Discussionmentioning
confidence: 99%
“…␤-Lactamase production by mycobacteria is likely to be an important factor in the expression of resistance to ␤-lactam antibiotics (11, 12). Indeed, ␤-lactams in combination with either clavulanic acid or other ␤-lactamase inhibitors have in vitro activity against mycobacteria not observed with either agent alone (5,7,8,31).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CA is a compound produced by Streptomyces clavuligerus that produces a progressive inhibition of the beta-lactamases, having already been proven effective against the beta-lactamase of the mycobacteria by Cynamon and Palmer (5,6) and by us with amoxicillin (3). After administration by the oral route to humans of 250 mg of CA, a concentration of 5.2 ji,g/ml is found in serum (9).…”
mentioning
confidence: 99%